ANALISIS PENGARUH PELATIHAN TERHADAP PENINGKATAN PRESTASI KERJA GURU PNS SLTP N 2 RAMBAH HILIR - Dahlan, Latifah (Jurnal Mahasiswa Prodi Manajemen Fakultas Ekonomi, 2016)
The purpose of this study was to determine: 1) To determine the attitudes of teachers towards training in junior high school N 2 Rambah Hilir.2) To determine the attitudes of teachers towards improvement of job performance of teachers in junior high school N 2 Rambah downstream. 3) To determine the effect of training on the performance of junior civil servant teachers N 2 Rambah downstream. The training was held at JSS N 2 Rambah Downstream is still based on an invitation from the Department of Education. Of positive responses junior civil servant teachers N 2 Rambah Downstream ie 50.00% answered Strongly Agree Agree and 50.00% said, it can be concluded that the training is dibutuhkan.Koesioner Job performance generated answers most of the respondents gave a positive answer to strongly agree 46, 67% and 45.93% disagree. The remaining 7.41% answered Neutral. They consider job performance can be improved either by training baik.Persamaan regression obtained as follows: Y = 14 816 + 0.552 X. This value indicates that the X or Y or training effect on Job Performance of 0.552 or 55.2% and Calculation obtained t count is 2,941 bigger than t table is 1.771. So that there is a positive effect of training on the achievements of junior civil servant teachers N 2 Rambah Hilir.Selanjutnya based on the calculation results obtained significance figure of 0,011. Figures 0.011 <0.05 then H rejected and H accepted. It means that there is a significant effect of training on the performance of junior civil servant teachers N 2 Rambah downstream. Therefore, there is the influence of variable X to variable Y.